Posisi Daya Saing Ekspor Kelapa Indonesia dalam Persaingan Negara Eksportir Dunia Tahun 2015–2024 - Marbudi; Abu Hasan As-Sadili; Varingan Prianando Tambunan; Anggita Dwi Oktaviani; Bina Unteawati (LPPM Universitas Malikussaleh - Indonesia, 2026)
The increase in the quantity of Indonesian coconut exports was not accompanied by an increase in export value. This condition indicates an indication of low competitiveness. Competitiveness is a general concept used to refer to market commitment to international competition. The purpose of this study is to analyze the trend in export volume and export value obtained by Indonesia and analyze the competitiveness of Indonesian coconut exports in the international market. The methods used in this study were descriptive analysis and RCA. The results of the study indicate that Indonesia has a high growth trend in the quantity of coconut exports but is not accompanied by an increase in export value. This condition is caused by efforts used to win the competition, namely setting low prices due to the availability of abundant raw materials and relatively cheap labor costs. Based on the results of the RCA analysis, Indonesia ranks fifth as the country with the lowest RCA index after Ivory Coast, Tanzania, Cambodia, and Vietnam. Low competitiveness is caused by weak implementation of minimum export price regulations and a lack of post-harvest technology development.